Formulasi Sediaan Masker Gel Peel Off Ekstrak Kulit Buah Apel Fuji (Malus domestica) Dengan Variasi Konsentrasi PVA (Polivinil Alkohol) - Besse Yuliana; Putri Damayanti Syahrir (Jurusan Farmasi Poltekkes kemenkes Makassar, 2026)
This study aimed to formulate a peel-off gel mask containing Fuji apple (Malus domestica) peel extract with various concentrations of PVA (Polyvinyl Alcohol) and to evaluate its stability and physical properties. Peel-off gel masks are known for their ability to help combat free radicals. Fuji apple peel was selected due to its high antioxidant content, such as flavonoids, quercetin, and other phenolic compounds that can effectively neutralize free radicals and promote skin health. The extraction of Fuji apple peel was performed using maceration with 70% ethanol as the solvent. The peel-off gel mask formulations were prepared with PVA concentrations of 10%, 12.5%, and 15%. The formulated masks were evaluated for their organoleptic properties, homogeneity, viscosity, pH, spreadability, drying time, stability (Cycling Test), and irritation potential. The results showed that all formulations met the required standards for organoleptic properties, homogeneity, pH, drying time, and showed no irritation. Formulations containing 12.5% and 15% PVA demonstrated optimal physical stability with acceptable viscosity, pH, and spreadability, along with a comfortable texture when applied to the skin. Based on these findings, Fuji apple peel extract can be formulated into a stable and safe peel-off gel mask at PVA concentrations of 12.5% and 15%.